Construction and Research of University Medical Laboratory Safety Education Management System - Yang, Xiulan; Dong, Xia (International Journal of Natural Resources and Environmental Studies, 2024)
University laboratories play a vital role in experimental teaching and scientific research. As the basis of laboratory safety management, laboratory safety education is an important means to eliminate hidden dangers and improve the level of laboratory safety management. Combining the characteristics and safety risks of medical laboratories, this study adheres to the goal of people-oriented and life-first safety management. Construct and innovate the medical laboratory safety education management system from five aspects: building laboratory safety responsibility system, improving laboratory safety management system construction, improving laboratory safety management and protection system, strengthening laboratory safety education and publicity system construction and implementing laboratory safety inspection and rectification system, and improve the effectiveness of laboratory safety education, improve the comprehensive quality and safety awareness of laboratory personnel, form a good safety atmosphere for medical laboratories, ensuring the safe and stable operation of medical laboratories, and help the "double first-class" construction of universities and the construction of healthy China.